Women in bicycle factories, 1908 (1908)
1908 1880-1914 "Women in bicycle factories, 1908" [EP0068], 1908 Leaflet distributed around Coventry in 1908, probably by the National Society of Amalgamated Brassworkers and Metal Mechanics, condemning the employment of women as polishers in bicycle factories.